Substituting Classic Procedures in Favor of Digital Procedures in Cases with Minors - Giurgea, Lenuta (Journal of Danubian Studies and Research, 2022)
In the current context, as a result of the spread of the COVID-19 pandemic, the need to develop a network that allows the creation of a suitable environment for the digitization of the judicial system is being discussed more and more frequently. The pandemic has brought to the surface the gaps in the judicial system regarding the entire digitization process. Thus, an example would be the norm that provided that the courts can communicate documents using the electronic signature and which was mostly inapplicable, because many courts were not equipped with this signature, although the recommendations were in the sense of sending the documents by post electronics . The lacunar legislative framework is a common problem that does not allow the development of a real possibility of creating and expanding viable digitization mechanisms that respect the procedural guarantees imposed by national and European legislation. Trying to summarize, we can say that technology comes to the aid of modern devices by diluting the classic procedure in favor of the digital procedure and regarding cases with minors. In civil matters, we show that the digitalization of justice in Romania has developed in an extremely slow manner compared to the need for freedom and evolution of humanity, but also a certain convenience of the people. In the context of the digitalization of society, we appreciate that it is normal for the legal profession to begin a transformational change towards new opportunities.